Genesis of the theory of geosystems: A comparative discussion of the russo-Soviet and French schools - Oliveira, Cristina Silva [UNESP]; Neto, Roberto Marques (Universidade Federal do Paraná, 2020)
Geosystemic theory does not integrate a stream of thought outlined by standardized concepts in geographical science. Conversely, at least two schools with different philosophical-methodological approaches appear with conceptual and interpretive proposals of the concept: the Russian-Soviet and the French. These schools seized by different angles the anthropic, spatial and scalar dimensions of the geosystem. The purpose of this study is to expose the genesis of the Russian-Soviet school and the French school of geosystems and show, in succinct terms, what distinguishes their ways of dealing with environmental and social problems. Next, a comparison will be made on their historical roots, theoretical influences, with particular attention to the attitude of each one to two questions that are fundamental in the study of geosystems: 1) how each school interprets the scalar question in its analyzes; 2) how each school explains the relationship between man and nature. The genesis of the precursor schools in the concept development is interpreted, focusing on the differences attributed to the environmental component and anthropogenic problems. Considering that the two schools of thought have developed independently, we seek from the explanations of the text to suggest that the exchanges between the two schools of thought be intensified, in order to contribute to a better understanding of the main issues. that permeate the paradigm of geosystems in geography.
Gênese da teoria dos geossistemas: Uma discussão comparativa das escolas russo-soviética e francesa
Keywords: Geosystems; Landscape studies; Man; Nature